PENERAPAN EMPAT ELEMEN KUNCI DALAM MATA PELAJARAN PENDIDIKAN PANCASILA PADA CAPAIAN PEMBELAJARAN DI FASE D KELAS VII - Sudrajat, Rahmat; Budi Astuti, Cahyaning (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2023)
Pancasila education in the 2022 curriculum is a new subject that must be applied by schools from the elementary, and junior high school/MTs, SMA/MA, and SMK/SMAK levels. The application of Pancasila Education subjects is given to all Grades, from 1 and 4 for elementary schools, class VII for junior high schools /MTs, and class X for SMA / MA and SMK / SMAK. Meanwhile, the other classes still use PPKn subjects. In the curriculum from the beginning of Indonesia's independence until now, in every curriculum in schools from 1947 until now the development of Pancasila Education is schooled (currently). It began with the name Moral (Curriculum 1947), Civic (Curriculum 1952), Moral Development (Curriculum 1964), State Citizenship Education / PKN (Curriculum 1968), Pancasila Moral Education / PMP (Curriculum 1975), Pancasila Moral Education with P-4 Content (Curriculum 1984), Pancasila and Citizenship Education / PPKn (Curriculum 1994), Citizenship / Kn (Curriculum 2004), Civic Education / Civics (Curriculum 2006), Pancasila and Citizenship Education / PPKn (Curriculum 2013) and finally Pancasila Education (Curriculum 2022). The purpose of the Pancasila Education Subject in the 2022 curriculum is to realize students who can have a noble character based on faith and devotion to God, understand the food and values of Pancasila, analyze the constitution and applicable norms, understand their identity as part of the Indonesian nation and analyze the characteristics of the Indonesian nation and local wisdom. Researchers on this occasion want to explore the four key elements contained in the Pancasila Education subject issued in the 2022 curriculum in phase D of class VII by describing four key elements of Learning Outcomes, compiling core materials, and compiling learning objectives